3y-(-4y+3)=-17

Simple and best practice solution for 3y-(-4y+3)=-17 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3y-(-4y+3)=-17 equation:


Simplifying
3y + -1(-4y + 3) = -17

Reorder the terms:
3y + -1(3 + -4y) = -17
3y + (3 * -1 + -4y * -1) = -17
3y + (-3 + 4y) = -17

Reorder the terms:
-3 + 3y + 4y = -17

Combine like terms: 3y + 4y = 7y
-3 + 7y = -17

Solving
-3 + 7y = -17

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '3' to each side of the equation.
-3 + 3 + 7y = -17 + 3

Combine like terms: -3 + 3 = 0
0 + 7y = -17 + 3
7y = -17 + 3

Combine like terms: -17 + 3 = -14
7y = -14

Divide each side by '7'.
y = -2

Simplifying
y = -2

See similar equations:

| (x-2)/6=(x+3)/9 | | 35-8x=22 | | 7(6+2)= | | -(5a+4)+1=2-(5a-1) | | -22.4+6x=75.5 | | t/-17.7=-12.7 | | -(2a-2)+3=3-(2a+5) | | 6(3-2)x=54 | | 5(a+4)-(4a+4)=4(5a-2)+5 | | 900=x-.5 | | 7(2y+7)+(-36y)= | | 6x^5-4x^2+10x=0 | | -6n-1n=16 | | x^8-2x=0 | | 8(-16)/2(-8)-5(-3) | | 4-4(2a-3)=0 | | 6-3|-8r-9|=-15 | | (2x-1)/(9-x^2) | | -3|9m+2|+10=10 | | y^1/6(y^11/6+y^23/6) | | log(x+1)+2*log(x)=log(x^2+8) | | 4-9|-6-b|=-14 | | 10-10|-8k+4|=40 | | 17/x+7 | | 7.6=p-6 | | -8|3-8k|=40 | | Ln(3x)+5=7 | | 2/7x14/3 | | 3|x/9|+7=8 | | 5(3x-2)-8(2x+3)-9=51 | | -2(2x+2)=4(2-x)-12 | | 2x^2+3=y |

Equations solver categories